PENGARUH RETURN ON ASSET, EARNING PER SHARE, PRICE EARNING RATIO, DEBT TO EQUITY RATIO, PRICE TO BOOK VALUE TERHADAP HARGA SAHAM PADA PERUSAHAAN INDEKS LQ 45 PERIODE 2010-2014 - Febriana Indah Pratiwi, 12.05.52.0096; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2016)
This research intend to test the effect of Return On Asset, Earning Per Share, Price Earning Ratio, Debt to Equity Ratio, and Price to Book Value to stock price listed in LQ 45 index. The populations on this research are the listed index in Indonesia Stock Exchange incorporated in index LQ 45 that observated on 2010-2014. The technique to determine sample is using purposive sampling method and the amount of selected sample are 186 companies. Analysis data technique that used is regression analysis. The result of research have shown that variables EPS and PBV gives significant impact to stock price, otherwise ROA, PER, and DER does not have significant effect to stock price.Keywords: Return On Asset, Earning Per Share, Price Earning Ratio, Debt To Equity Ratio, Price To Book Value, LQ 45 Index Stock Price